THE MOTIVATIONAL THEORIES AND CONSUMER BEHAVIOR: A THEORETICAL REVIEW ABOUT METAMOTIVATION AND HEDONISM (Revista ADMPG, 2026)
This paper intended to provide an extended theoretical review about motivational theories, theirrole in the consumer behavior and, eventually, how metamotivation is initiated and its relationto hedonism. It’s visible to see the importance of Maslow (1943;1954;1967;1968;1970;1971) andFestinger (1957;1959) in the construction of this field of study, as well how big the perceptionthat many segments have benefited from these researches is. The main conclusion of the articleis the close relation between the metamotivations and the hedonism. As advises for furtherresearch, this study suggests academics to develop assignments covering Maslow’s D-valuesand B-values and to conduct researches regarding metahedonism.